Prioritizing Land and Water Interventions for Climate-Smart Villages - Alam, Mohammad Faiz; Sikka, Alok (Wiley, 2019)
Climate-smart villages mean implementing a portfolio of best locally suited climate-smart agricultural practices in an integrated manner to build resilience of the local community. Land and water interventions form a crucial part of a climate-smart agricultural practices portfolio, with water availability being the key limiting factor of crop growth. To aid in this decision-making process of prioritizing land and water interventions, a simple and robust spreadsheet tool based on a water balance is developed. The tool integrates and simulates impacts of land and water interventions on the water balance to determine their impact across climate-smart agricultural objectives of agricultural productivity, climate change adaptation and mitigation. The tool was implemented in two villages in the state of Madhya Pradesh, India. The tool performs well in simulating village water balance and its impact on the yield of rainfed and irrigated crop areas. Results show that considerable differences exist within the portfolio of land and water interventions, with only a combination of supply, demand and moisture conservation practices being able to help achieve climate-smart agricultural objectives. In the best case scenario, yield can be increased by up to 10% and greenhouse gas emission intensity reduced up to 17%. Comparison with stakeholder perception analysis highlights the utility of this tool in providing additional quantitative information in the decision-making process.